The role of hematopoietic stem cell transplantation for relapsed and refractory Hodgkin lymphoma. Issue 2 (24th November 2014) - Kako, Shinichi; Izutsu, Koji; Kato, Koji; Kim, Sung‐Won; Mori, Takehiko; Fukuda, Takahiro; Kobayashi, Naoki; Taji, Hirofumi; Hashimoto, Hisako; Kondo, Tadakazu; Sakamaki, Hisashi; Morishima, Yasuo; et al.
<x xml:space="preserve">Abstract</x> The optimal treatment strategy with the use of hematopoietic stem cell transplantation (HSCT) for relapsed and refractory Hodgkin lymphoma (HL) remains unclear. We performed a retrospective analysis using registry data from the Japanese Society for Hematopoietic Cell Transplantation. Adult patients with HL who underwent a first autologous or a first allogeneic HSCT between 2002 and 2009 were included. Patients who underwent HSCT in first complete remission (CR) were excluded. Autologous and allogeneic HSCT were performed in 298 and 122 patients, respectively. For autologous HSCT, overall survival at 3 years (3yOS) was 70%, and sex, age, disease status, and performance status (PS) at HSCT were prognostic factors. OS was favorable even in patients who underwent autologous HSCT in disease status other than CR. For allogeneic HSCT, 3yOS was 43%, and sex and PS at HSCT were prognostic factors. Disease status at HSCT, previous autologous HSCT, and conditioning intensity did not affect OS. Moreover, graft‐versus‐host disease did not affect progression‐free survival or relapse/progression rate. A first allogeneic HSCT without a previous autologous HSCT was performed in 40 patients. 3yOS was 45%, and was significantly inferior to that in patients who underwent their first autologous HSCT. This result was retained after the correction by the different patient characteristics according to the type of HSCT. In conclusion, autologous HSCT is effective in prolonging survival in patients with relapsed and refractory HL. Allogeneic HSCT might be beneficial even to relapsed HL after autologous HSCT, although establishing the role of allogeneic HSCT remains a challenge. Am. J. Hematol. 90:132–138, 2015. © 2014 Wiley Periodicals, Inc.